Solve the problem of assignment by using multi-Objective programming - ابراهيم سميرة خليل; جاسم امجد عبد الحسين (Journal of Economics and Administrative Sciences, 2018)
he assignment model represents a mathematical model that aims at expressing an important problem facing enterprises and companies in the public and private sectors, which are characterized by ensuring their activities, in order to take the appropriate decision to get the best allocation of tasks for machines or jobs or workers on the machines that he owns in order to increase profits or reduce costs and time As this model is called multi-objective assignment because it takes into account the factors of time and cost together and hence we have two goals for the assignment problem, so it is not possible to solve by the usual methods and has been resorted to the use of multiple programming The objectives were to solve the problem of assignment of real data, which was approved by the Kut textile factory, where the data included two important factors, namely cost and time factors. The problem was solved in( Win-QSb) by the special methods of allocation problem. The results revealed that the cost of allocating workers to machines is (248.60) thousand dinars The allocation time is (202) hours and also the mathematical model was built for the problem of multi-objective assignment and its solution using multi-objective programming. The results showed that the allocation cost is (230) thousand dinars and allocation time is (162) hours, The above results show that multi-objective programming is better than special methods to solve assignment problems.